SIGNIFICANCE OF THE GERMAN LANGUAGE TODAY - Bisenbaeva is the daughter of Nargiza Aytbay (Journal of new century innovations, 2023)
Abstract: Globalization processes taking place all over the world have made it clear how necessary sociolinguistic research is in the case of world languages and the expansion of the German language.